Electrochemical detection of aniline: an electrochemically initiated reaction pathway. - Hugo Seymour, E; Lawrence, N; Beckett, E; Davis, J; Compton, R (2002)
The electrochemically initiated reaction of aromatic amines with catechol has been examined as a facile route to the electrochemical determination of the former. The effects of the different structural isomers of sulfanilic acid on the analytical system has been studied and appraised. The report illustrates how by varying oxidation times of the catechol species or by increasing the number of repetitive voltammetric scans from one to four the analytical parameters (linear range and limit of detection) can be improved. The results provide a linear detection range of 2-40 muM for aniline with a corresponding limit of detection of 1.4 muM. The efficacy of the approach has been shown by a 99.5% (RSD=5.5%, N=5) recovery of 2.47 muM spiked aniline in river water.